Unraveling Turnover: QWL, Job Insecurity, and Commitment in Production Departments: Membongkar Tingkat Pergantian: QWL, Ketidakamanan Kerja, dan Komitmen Organisasi di Departemen Produksi - Anneke Mujiati; Dewi Andriani (Academia Open, 2022)
This study aimed to investigate the impact of Quality of Work Life (QWL), Job Insecurity (JI), and Organizational Commitment (OC) on Turnover Intention (TI) among employees in the production department of an industrial setting. The research was motivated by the observed increase in the turnover rate of the organization over a three-year period. Employing quantitative methods, data were collected and analyzed using statistical techniques. The sample consisted of employees in the production section, and a non-probability sampling technique was employed. The findings revealed that QWL exhibited a partial negative effect on TI, JI displayed a partial positive effect on TI, and OC showed a partial negative effect on TI. These results emphasize the importance of enhancing QWL, reducing job insecurity, and fostering organizational commitment to mitigate turnover intention among employees. The study contributes to the existing literature on employee turnover and provides practical implications for organizations striving to retain a satisfied and committed workforce. Highlights: Quality of Work Life and Organizational Commitment: The study examines how the quality of work life and organizational commitment influence turnover intention among employees in the production department. Job Insecurity as a Predictor: Job insecurity is identified as a significant factor contributing to turnover intention in the production department. Implications for Retention Strategies: The findings highlight the need for organizations to enhance work-life quality, reduce job insecurity, and foster organizational commitment to mitigate turnover intention among production department employees. Keywords: Turnover intention, Quality of Work Life, Job insecurity, Organizational commitment, Production department.